Entre a proteção legal e o direito à educação das pessoas com autismo: caminhos para a efetivação de políticas públicas para uma inclusão escolar digna - Fernandes, Helaine Cristina Pinheiro (2025)
The school inclusion of individuals with Autism Spectrum Disorder (ASD) in regular schools is a constitutional guarantee. However, its realization requires public policies that foster an inclusive educational structure to uphold this fundamental right. This dissertation analyzes the barriers to the full realization of the right to education and school inclusion for autistic individuals, highlighting that despite existing constitutional protection, there is a lack of effective public policies to genuinely promote school inclusion. This deficiency leads to discrimination and segregation in the school environment, violating the dignity and rights of these individuals. Truly inclusive education should not be limited to compliance with legal norms mandating enrollment but must also ensure the permanence, development, and participation of students, respecting equality and promoting their autonomy. Based on these premises, this study aims to reflect on the school inclusion process for individuals with autism in regular schools, assess the current state of the right to education for individuals with autism, and raise awareness of the legislative principles related to the topic. Furthermore, it seeks to emphasize the need for effective public policies to enforce the right to education for individuals with autism, such as providing specialized aides, training for school education professionals, utilizing appropriate resources, and implementing curricular adaptations. In alignment with this analysis, the study identifies critical points in the inclusion process, demonstrating the necessity of pathways for implementing public policies through the lens of the metatheory of fraternal law and through provoked judicial functions via structural litigation. Using the deductive method, the study was conducted through bibliographic and documentary research. Regarding the procedures, it is an exploratory study. As for its objectives, it is a descriptive analysis with a qualitative approach derived from legal doctrine, jurisprudence, and norms related to the rights of individuals with autism, highlighting the harms caused by the absence of effective public policies to implement these rights. The research aligns with the metatheory of fraternal law, examining not only existing theories within the legal field but also intersecting issues in psychiatry, psychology, and education through an intradisciplinary study method. This approach aims for a high level of critical analysis and incorporates the paradigm of fraternal law to propose an integrative framework that combines the values of solidarity, fraternity, equality, liberty, and the human dignity of autistic students. Consequently, due to the inefficiency of effective public policies aimed at inclusive education for individuals with autism, a state of non-compliance far from the ideal legal standard is observed, impacting the entire community structurally. This underscores the need for coordinated actions between public authorities and civil society, highlighting the role of structural processes in the effectiveness of judicial protection to promote inclusive education. The results indicate that overcoming the barriers to educational inclusion requires strengthening public policies that ensure access, permanence, and full educational development for individuals with ASD, consolidating the right to inclusive education as an essential tool for building a more just, supportive, and equitable society.